ANALISIS KESALAHAN KEMAMPUAN BERPIKIR KREATIF SISWA MTs DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL - Ade Hernawan; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research was conducted with the aim of finding out the errors in the creative thinking ability of MTs students in solving Social Arithmetic problems due to the low level of mathematical creative thinking. This research was conducted by one class VII MTs students in one of the MTs in West Bandung Regency who had implemented the 2013 curriculum. The analytical creative thinking ability has indicators that include fluency, flexibility, originality and elaboration. The data collection technique used is in the form of a 4-question test result in the form of a description of the social arithmetic material, then a description of the errors in each question number. The data analysis carried out is data reduction, data presentation and conclusion drawing. The conclusion obtained from the results of this study is that the creative thinking ability of MTs class VII students in one of the MTs in West Bandung Regency has a fairly creative category and students' mistakes in solving social arithmetic problems are the lack of finding new ideas and using various methods or completion steps and mistakes. in understanding the problem due to a lack of deeper understanding of the material.